PRINSIP-PRINSIP DASAR TENTANG HAK PERLINDUNGAN ANAK - B, Muhaemin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
The words of the Quran and the authentic traditions of Prophet Muhammad, contain the rights and responsibilities granted by God to humankind. These unique rights mentioned in Islam also include the rights of children. Children’s rights are not guaranteed by the actions of their parents, their communities, or even their governments. God Himself guarantees children’s rights. Children have the right to be fed, clothed and protected until they reach adulthood. The child has the right to a good education and a stable environment in which to grow up. Boys and girls, as well as orphans, possess these rights in full. Nevertheless God and Holy Prophet Muhammad gave parent certain obligations to assure children's rights.